Measurements of ion mobility in argon and neon based gas mixtures - Deisting, Alexander; Vranic, Danilo (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
As gaseous detectors are operated at high rates of primary ionisation, ions created in the detector have a considerable impact on the performance of the detector. The upgraded ALICE Time Projection Chamber (TPC) will operate during LHC Run 3 with a substantial space charge density of positive ions in the drift volume. In order to properly simulate such space charges, knowledge of the ion mobility K is necessary. To this end, a small gaseous detector was constructed and the ion mobility of various gas mixtures was measured. To validate the corresponding signal analysis, simulations were performed.
Available online 18 June 2016
Gesehen am 09.10.2018